Prevention of Diabetic Complications by Walnut Leaf Extract via Changing Aldose Reductase Activity: An Experiment in Diabetic Rat Tissue - Zahra Abbasi; Gholamali Jelodar; Bita Geramizadeh (Journal of Diabetes Research)
Background. Increased activity of aldose reductase (AR) is one of the mechanisms involved in the development of diabetic complications. Inhibiting AR can be a target to prevent diabetes complications. This study is aimed at evaluating the effect of cyclohexane (CH) and ethanol extracts (ET) of walnut leaves on AR activity in the lens and testis of diabetic rats. Methods. Fifty-six male rats classified into seven groups as control and treatment groups and treated for 30 days. The treatment groups were treated with different concentrations of ET and CH. The diabetic control (DC) group was exposed to streptozotocin. AR activity was measured in the lens and testis. The expression of AR in the testis was evaluated by the immunohistochemistry method. Results. Both extracts significantly reduced the AR activity (ng/mg of tissue protein) in the testis (0.034±0.004, 0.038±0.010, and 0.040±0.007 in the treatment groups vs. 0.075±0.007 in the DC group) and lens (1.66±0.09, 2.70±0.47, and 1.77±0.20 in the treatment groups vs. 6.29±0.48 in the DC group) of the treatment group compared to those of the DC group (P<0.05). AR expression in the testes of the treatment groups was decreased compared with that of the DC group (P<0.0001). Conclusion. Walnut leaf extracts can reduce the activity and localization of AR in the testes and its activity in the lens of diabetic rats.